Children's media practices: challenges and dilemmas for the qualitative researcher. Issue 1 (2nd January 2016) - Aarsand, Pål
Abstract: The commentary discusses some of the challenges and dilemmas social researchers face when they investigate children's media practices in present and future Western societies. The paper draws on ethnography's and ethnomethodology's experience of using video recordings as primary data and their commitment to prioritising the participants' perspective(s). First, it is argued that one of the main challenges for social researchers is to obtain data that make it possible to broaden our understanding of media practices that are both trans-local and multimodal. Second, it is argued that new media interfaces make it particularly important to understand visual data and describe children's media practices. Third, this means that researchers will face new challenges and dilemmas with respect to choosing images, and deciding when and how to use them and what one wants to illustrate. Even more important, this will most likely increase the importance of research ethics when the quality of research as a professional practice is discussed.